A change of heart? A bivariate probit model of international students' change of return intention - Soon, Jan Jan (Feng Chia University, Taiwan, 2010)
Using a bivariate probit model on a sample of 623 international students studying at tertiary-level courses in New Zealand universities, this paper identifies the factors that affect the change in the students' intention of whether or not to return to their home countries after completing their studies.